A legal study on inquiry procedure under the registration of Pharmacists Act 1951 and its regulations / Nurul Afifah Osman - Osman, Nurul Afifah (2018)
In Malaysia, pharmacist’s misconduct cases are handled by Pharmacy Board Malaysia using existing inquiry process provides under the Registration of Pharmacists Act 1951 and its regulations. However, the implementation of the procedure has a limitation in certain aspects. Therefore, this research is to examine and compare the current laws on inquiry procedure for pharmacists between Malaysia and United Kingdom so as to highlight the inadequacies of the law in Malaysia. Subsequently, it is to recommend the methods in order to improve the current procedure. This research adopted qualitative research methodology where the information gathered from journals, reports, articles, books and a semi-structured interview. From this research, it was discovered that provisions in the Registration of Pharmacists Act 1951 are inadequate to assist the Pharmacy Board Malaysia in implementing the inquiry procedure for pharmacists. The obvious lacking is the absence of the definition of ‘infamous and disgraceful conduct’. Besides that, there are differences between Malaysia and United Kingdom in term of appointment of Board’s Members and no provision on notification to the complainant and interim order as compared with Pharmacy Order in the United Kingdom. Thus there is a need to improve on the administrative and legislative with regard to implementation of inquiry procedure in Malaysia.